Defining Antibiotic Inertia: Application of a Focused Clinical Scenario Survey to Illuminate A New Target for Antimicrobial Stewardship During Transitions of Care. (1st October 2021) - Kooda, Kirstin; Bellolio, Fernanda; Dierkhising, Ross; Tande, Aaron J
Abstract: In clinical scenario surveys, inpatient providers were more likely to report continuing inappropriate (odds ratio, 2.02 [95% confidence interval, 1.35–3.03]; P <.001) or broad-spectrum (1.8 [1.27–2.56]; P =.001) antibiotic therapy when initiated by emergency department providers, than to change to appropriate or narrow-spectrum therapy, respectively. Antibiotic inertia could represent a significant antibiotic stewardship target.